Anticancer evaluation of Myo-inositol through carbonic anhydrase IV inhibition activity: A spectroscopic, quantum computational, topological, drug-likeness and in-silico molecular docking studies - K. Rajkumar; V. Gokulakrishnan; S. Anand; R. Durga; G. Senthilkumar; S. Sri Karthick; R. Kayalvizhi Kothai (Results in Chemistry)
Numerous inositol isomers, particularly myo-inositol, are beneficial in the treatment of polycystic ovary syndrome, diabetes, anxiety, and depression. This study established that myo-inositol has the potential to be utilized as a carbonic anhydrase IV inhibitor to treat cancer. In this context, its structural parameters, vibrational assignments, and electronic transitions were investigated using both theoretical and experimental methods. The simulation of frontier molecular orbitals provides insight into energy gap and chemical stability. A strong correlation exists between experimental data and theoretical values, indicating that myo-inositol is highly stable. Understanding the charge distribution, localized electrons and weak interaction sites was achieved through molecular electrostatic potential surface, electron localization function, local orbital locator and reduced density gradient analyses. Only hydrogen and oxygen atoms are susceptible to nucleophilic and electrophilic attack due to Fukui analysis, which highlights their favorable sites. The drug-likeness, SwissTargetPrediction, and PASS Targets studies recommended myo-inositol as a potential carbonic anhydrase IV inhibitor. Molecular docking studies revealed that the research compound fits into the binding pocket of carbonic anhydrase IV, has a good dock score, and might be used as an anticancer drug when assessed alongside the reference compound, acetazolamide. Ultimately, high binding scores from in-silico molecular docking could facilitate the identification of new carbonic anhydrase IV inhibitors for the treatment of cancer.